RELATIONSHIP BETWEEN HUMAN CAPITAL AND MSMES PERFORMANCE WITH COMPETITIVE ADVANTAGE AS A MEDIATION - Rokhman, M. Taufiq Noor; Ratnawati, Ratnawati; Rahayu, Yayuk Ngesti (Universitas Brawijaya, Indonesia, 2023)
The numerous batik industries in Indonesia, including the province of East Java, are evidence of the fast-paced growth of batik in that country. Batik Businesses in East Java continue to perform poorly due to management issues that are numerous and interconnected. The resource-based theory emphasizes internal elements in elucidating business strategy through competitive advantage as a variable that influences the impact of human capital on the performance of Batik SMEs in East Java. The sampling strategy used in this research was proportional random sampling, with numbered samples drawn from 140 East Javan batik SMEs. A structural equation modeling (SEM) study demonstrates how human capital affects MSMEs' performance and competitive advantage. The link between human capital and the success of batik MSMEs in East Java can be mediated by competitive advantage. Based on the research findings, suggestions are put forward for science. The results of this research can enrich references and scientific repertoire related to Resource-Based Theory and can be implemented in MSMEs who want to get good performance by owning, mastering, and utilizing intangible assets through human capital. Batik SMEs in East Java need to improve leadership skills to be more cooperative with employees and partners and improve relations between employees, partners, and consumers, for further researchers can conduct a study of the business environment and network (networking) efforts to improve the performance of MSMEs.